2008
DOI: 10.1021/jm701491k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of NO-Donor-Tacrine Hybrids as Hepatoprotective Anti-Alzheimer Drug Candidates

Abstract: In search of safer anti-Alzheimer drugs, 14 NO-donor-tacrine hybrids (1- 14) were synthesized and evaluated for their ability to inhibit cholinesterases and for vasorelaxation effects. Compounds 1- 13 showed good cholinesterases inhibitory activities in vitro, while 14, particularly, was highly selective, preferring butyrylcholinesterase rather than acetylcholinesterase. Four selected compounds (1, 9, 11, and 14) moderately relaxed the porcine pulmonary arteries in organ bath. In the hepatotoxicity study, sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 34 publications
2
61
0
Order By: Relevance
“…There are several reports in the literature on nitrate hybrid molecules: nicorandil, a potassium channel opener with nitrate function [10,11]; 2NTX-99, a thromboxane synthase inhibitor and thromboxane receptor antagonist and NO-releasing group [12]; GT-094, a nonsteroidal anti-inflammatory drug with NO function [13]; the antifungal drug ketoconazole with a diazen-1-ium-1,2-diolate or an organic nitrate moiety [14]; NO-donor-tacrine hybrids as hepatoprotective anti-Alzheimer drug candidates [15]; the NicOx compound nitroaspirin, reviewed in Gresele and Momi [16]; NO-releasing celecoxib analogs, inhibitors of inducible cyclooxygenase [17]; a vitamin E analog with NO donor function [18]. Probably we could not list all examples that have been published during the last few years but our list provides an overview of the diversity of NO hybrids.…”
Section: Characterization Of New Organic Nitrate Hybrid Drugs Covalenmentioning
confidence: 99%
“…There are several reports in the literature on nitrate hybrid molecules: nicorandil, a potassium channel opener with nitrate function [10,11]; 2NTX-99, a thromboxane synthase inhibitor and thromboxane receptor antagonist and NO-releasing group [12]; GT-094, a nonsteroidal anti-inflammatory drug with NO function [13]; the antifungal drug ketoconazole with a diazen-1-ium-1,2-diolate or an organic nitrate moiety [14]; NO-donor-tacrine hybrids as hepatoprotective anti-Alzheimer drug candidates [15]; the NicOx compound nitroaspirin, reviewed in Gresele and Momi [16]; NO-releasing celecoxib analogs, inhibitors of inducible cyclooxygenase [17]; a vitamin E analog with NO donor function [18]. Probably we could not list all examples that have been published during the last few years but our list provides an overview of the diversity of NO hybrids.…”
Section: Characterization Of New Organic Nitrate Hybrid Drugs Covalenmentioning
confidence: 99%
“…Concerns about hepatotoxicity, due to oxidative damage from metabolism of tacrine (Osseni et al 1999;Dogterom et al 1988 ) , prompted the search for newer compounds that would have the same or better effects on A b aggregation, without toxicity. Among the newer agents are tacrine-antioxidant hybrid molecules, such as lipocrine, which contains a lipoic acid moiety (Rosini et al 2005), and tacrine hybrids that contain NO donors (Fang et al 2008 ) . Another source of concern was inhibition of butyrylcholinesterase (BuChE) activity outside of the CNS by AChE inhibitors.…”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 99%
“…30 Simultaneous modulation of several pathological events of the ongoing disease may then contribute to therapeutic effect of progressing AD. 31 The MTDL approach has been employed by many research groups [32][33][34][35] and has shown success, for example in the case of the compound ladostigil 36 which has reached clinical trials. 37 Exploiting the advantage of conjunctive approach, we designed a series of compounds combining known scaffolds of MAO and ABAD inhibitors to introduce MAO inhibitory activity into frentizole moiety and explore structural inhibitory features of both MAO and ABAD scaffolds.…”
Section: Introductionmentioning
confidence: 99%